Pengaruh Implementasi Sertifikasi SVLK, Karakteristik Produk dan Tujuan Ekspor Terhadap Harga Premium Ekspor Kayu Olahan Indonesia - Aditya Rahman Azis Aditya Rahman Azis; Vid Adrison (Cendekia Niaga, 2021)
Premium price is an indicator of certification market effectiveness. But its existence depends on the eco-consumers in the markets. Ideally, certification is in line with benefits obtained from the market. This research aims to analyze whether the SVLK certification is capable to generate premium price of Indonesian mouldings exports and see if there is a different effect between EU and Non-EU export destinations. The analysis base on transactional exports data from 2006 to 2017 using the hedonic model approach. The regression results show that the price of SVLK certified products is 7% more expensive than non-certificate products. However, there is no significant influence of the export destination to EU or Non-EU to the prices.